Effects of Phospholipase Dε Overexpression on Soybean Response to Nitrogen and Nodulation - Yao, Shuaibing; Wang, Geliang; Wang, Xuemin (Frontiers in Plant Science, 2022)
Nitrogen is a key macronutrient to plant growth. We found previously that increased expression of phospholipase D (PLD), which hydrolyzes phospholipids into phosphatidic acid (PA), enhanced plant growth under nitrogen deficiency in Brassicaceae species Arabidopsis and canola. The present study investigated the effect of PLD-overexpression (OE) on soybean (Glycine max), a species capable of symbiotic nitrogen fixation. PLD-OE led to a higher PA content in leaves under nitrogen-sufficient and -deficient conditions than wild-type. PLD-OE soybean plants displayed increased root length and leaf size, and the effect of PLD-on leaf size was greater under nitrogen-deficient than -sufficient condition. Under nitrogen deficiency, PLDOE soybean plants had a higher chlorophyll content and activity of nitrogen assimilation-related enzymes than wild-type soybean plants. PLD-OE soybean plants also increased seed production under nitrogen deprivation with and without nodulation and decreased seed germination in response to high humidity storage and artificial aging. These results suggest that PLD promotes nitrogen response and affects adversely seed viability during storage.